Monitoring technical tennis performance under increasing physical intensity by the PTTF-test - Michel Smit; Marije Elferink-Gemser; Nikki Kolman; Barbara Huijgen (Universidad de Granada, 2021)
Monitoring technical skills under increasing physical intensity is important for determining a player's performance level in tennis. Therefore, the aim of this study was to determine to what extent the new Physical Technical Tennis-specific Field test (PTTF-test) was able to capture fluctuations in technical skill under increasing physical intensity in adolescent talented tennis players. Forty adolescent players (21 males, 19 females, mean age = 15.4 years) performed the PTTF-test until exhaustion (i.e., when they were not able to hit two subsequent oncoming balls with an adequate technique). Technical skills (stroke velocity, stroke accuracy, VA-index and percentage errors) were compared between physical intensity levels, age categories and genders. For all age categories and genders, physical intensity (heart rate) increased between the 'BASELINE'-situation and the 'FINAL'-situation (p<.001). All technical skills, i.e. stroke velocity, stroke accuracy, VA-index and percentage errors, decreased when comparing the FINAL intensity level to the BASELINE intensity level (p<.001). Players in older age categories (16+) reached a higher PTTFlevel and exhibited lower mean heart rates than players in the youngest age category (U14) in both the 'BASELINE'-situation and the 'FINAL'-situation depending on the level players reached (p<.01). These findings show that the PTTF-test is able to analyse and monitor the performance of technical skills under increasing physical intensity in adolescent talented tennis players.